Pastoral livelihood pathways transitions in northern Kenya: The process and impact of drought - Kirui, L.K.; Jensen, Nathaniel D.; Obare, G.A.; Kariuki, I.M.; Chelanga, Philemon; Ikegami, M. (Springer, 2022)
Recurrent droughts and long-term changes to climate, social structures, and the economy in the world’s arid and semi-arid lands have impacted pastoralists’ livelihood activities over time, resulting in different livelihood pathways. Some pastoralists continue to follow more traditional strategies of herd accumulation, while others frequently engage in livestock markets and value addition activities, and others still are dropping out of pastoralism. Using data collected over 6 years from 924 households in northern Kenya and applying a generalized structural dynamic multinomial logit model, this study quantitatively determined the dynamic transitions between livelihood categories conditional on drought incidences. From the results, there were considerable and frequent transitions between livelihood pathways within the panel period (2009–2015). Notably, many households that started in the low-cash income, larger herd size category denoted as hanging in, were transitioning to lower cash income with small herds (dropping out). At the same time, there was a great deal of back and forth between the category with low-cash income and small herd size (dropping out) and the category with higher cash income and small herd size (moving out), indicating that moving out was the only way out of poverty. Also, an increase in vegetation index from a drought season where the index was at a 10% level to a good season where the level was 90% decreased the likelihood of households dropping out from a predicted probability of 37.9 to 28.7% and increased the likelihood of moving up and moving out from 22.2 to 25.0% and 22.6 to 34.3%, respectively, unconditionally. The study findings imply that any livelihood interventions aimed at reducing the impact of drought and alleviating poverty among pastoral households should support the transition to market-oriented, relatively successful pathways and also protect households from falling back into the ranks of poverty by dropping out.